'Our Care through Our Eyes': a mixed-methods, evaluative study of a service-user, co-produced education programme to improve inpatient care of children and young people admitted following self-harm. Issue 12 (29th December 2015) - Manning, Joseph C; Latif, Asam; Carter, Tim; Cooper, Joanne; Horsley, Angela; Armstrong, Marie; Wharrad, Heather
Abstract : Introduction: Within Europe, the UK has one of the highest rates of self-harm, with a particularly high prevalence in children and young people (CYP). CYP who are admitted to paediatric hospital wards with self-harm are cared for by registered children's nurses who have been identified to lack specific training in caring for this patient group. This may impede the delivery of high quality care. Therefore, this study aims to co-produce, implement and evaluate an education programme for registered children's nurses to improve their knowledge, attitudes and confidence when caring for CYP admitted with self-harm. Methods and analysis: This mixed-methods evaluative study will involve a three-stage design. Stage 1: A priority-setting workshop will be conducted with 19 registered children's nurses. A Delphi technique will be used to establish consensus of information needs. Stage 2: An online educational intervention will be co-produced with 25 CYP and 19 registered children's nurses based on the priorities identified in Stage 1. Stage 3: The intervention will be implemented and evaluated with 250 registered children's nurses at a single hospital. Online Likert scale questionnaires will be administered at baseline and postintervention to assess levels of knowledge, attitudes and confidence in caring for CYP who self-harm. Descriptive and inferential statistics will be used to analyse the data. Statistical significance will be assessed at the 5% (two-sided) level. One-to-one qualitative interviews will also be undertaken with approximately 25 participants to explore any perceived impact on clinical practice. An interpretive descriptive approach will guide qualitative data collection and analysis. Ethics and dissemination: This study aims to develop, trial and evaluative a service-user, co-produced education programme for acute hospital registered children's nurses to improve the care of CYP admitted due to self-harm. The study has ethical approval from the National Health Services Research Ethics Committee and full governance clearance.